2022
DOI: 10.1101/2022.11.07.515398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating the effect of ankle plantarflexion and inversion-eversion exoskeleton torques on center of mass kinematics during walking

Abstract: Walking balance is central to independent mobility, and falls due to loss of balance are a leading cause of death for people 65 years of age and older. Bipedal gait is inherently unstable, but healthy humans use corrective torques to counteract perturbations and stabilize gait. Exoskeleton assistance could benefit people with neuromuscular deficits by providing stabilizing torques at lower-limb joints to replace lost muscle strength and sensorimotor control. However, it is unclear how applied exoskeleton torqu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…The study showed reasonable model validity for muscle activation and VL muscle fascicle velocities across different power demands and cadence conditions. Recent studies that used a direct collocation approach during walking (Bianco et al 2022) and hopping (Jessup, Kelly, and Cresswell 2023) showed a similar correspondence to experimental data. The Umberger metabolic probe also revealed a curvilinear pattern in relationship between cadence and metabolic power for all intensities, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 65%
“…The study showed reasonable model validity for muscle activation and VL muscle fascicle velocities across different power demands and cadence conditions. Recent studies that used a direct collocation approach during walking (Bianco et al 2022) and hopping (Jessup, Kelly, and Cresswell 2023) showed a similar correspondence to experimental data. The Umberger metabolic probe also revealed a curvilinear pattern in relationship between cadence and metabolic power for all intensities, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 65%
“…However, ground truth joint angles and moments cannot be directly measured from experiments. We thus used a three-dimensional dynamic simulation of walking created using trajectory optimization [ 63 ], where joint angles and moments are known and residual forces and moments are also known to be zero, to generate a synthetic dataset. We used synthesized marker trajectories, along with the computed ground reaction forces and centers of pressure from the simulation, as inputs to AddBiomechanics.…”
Section: Methodsmentioning
confidence: 99%
“…During the initial phase of SLS, the CoM moves laterally toward the supporting (SLS) leg to prepare for swinging of the opposite leg, therefore, lateral stability is challenged in the frontal plane 44 . Ankle inversion torque generated by the TA muscle during single leg stance shifts the center of pressure (CoP) laterally 45 . Given that the CoP should be continuously moved toward the CoM to keep the CoM over the base of support for maintaining balance, the older adults-speci c predominant TA activation appears to be one of the movement strategies for lateral balance control at the ankle joint level.…”
Section: Age-related Differnces In Knee Extensor Eccentric Control An...mentioning
confidence: 99%